Essays on macroeconomic effects of fiscal policy rules - Jukka Railavo (Bank of Finland, 2006)
Economic and Monetary Union (EMU) can be characterised as a complicated set of legislation and institutions governing monetary and fiscal responsibilities.The measures of fiscal responsibility are to be guided by the Stability and Growth Pact (SGP), which sets rules for fiscal policy and makes a discretionary fiscal policy virtually impossible.To analyse the effects of the fiscal and monetary policy mix, we modified the New Keynesian framework to allow for supply effects of fiscal policy.We show that defining a supply-side channel for fiscal policy using an endogenous output gap changes the stabilising properties of monetary policy rules. The stability conditions are affected by fiscal policy, so that the dichotomy between active (passive) monetary policy and passive (active) fiscal policy as stabilising regimes does not hold, and it is possible to have an active monetary - active fiscal policy regime consistent with stability of the economy.We show that, if we take supply-side effects into account, we get more persistent inflation and output reactions.We also show that the dichotomy does not hold for a variety of different fiscal policy rules based on government debt and budget deficit, using the tax smoothing hypothesis and formulating the tax rules as difference equations. The debt rule with active monetary policy results in indeterminacy, while the deficit rule produces a determinate solution with active monetary policy, even with active fiscal policy.The combination of fiscal requirements in a rule results in cyclical responses to shocks.The amplitude of the cycle is larger with more weight on debt than on deficit.Combining optimised monetary policy with fiscal policy rules means that, under a discretionary monetary policy, the fiscal policy regime affects the size of the inflation bias.We also show that commitment to an optimal monetary policy not only corrects the inflation bias but also increases the persistence of output reactions.With fiscal policy rules based on the deficit we can retain the tax smoothing hypothesis also in a sticky price model.
URN:NBN:fi:bof-201408071690
Keywords: 330; inflation; fiscal policy; fiscal policy rules; optimalmonetary policy; policy coordination; stabilisation; Eurozone; Finanzpolitik; Öffentliche Schulden; Geldpolitik; Inflation; EU-Staaten; Europäischer Stabilitätsmechanismus; Wirkungsanalyse